1999
DOI: 10.1007/s002709900391
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic chemoembolization: Effect of intraarterial lidocaine on pain and postprocedure recovery

Abstract: Intraarterial lidocaine during chemoembolization reduces the severity and duration of pain after chemoembolization resulting in faster recovery thus reducing the length of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Four studies 19Y22 reported statistically significant decreases in frequency and dose for both procedural and postprocedural analgesia requirements when using IA lidocaine. Two studies 19,22 However, both studies reported low incidences of grades 2 and 3 RUQP after TACE, and although IA lidocaine was included in the preprocedure medication regimen and may have contributed to RUQP management, these findings must be interpreted with caution as multiple interventions were implemented, and neither study attributes their findings to pre-TACE IA lidocaine alone. It must also be noted that only 3 studies 20Y22 used a visual analog scale as a subjective measurement of pain.…”
Section: Intra-arterial Lidocainementioning
confidence: 96%
“…Four studies 19Y22 reported statistically significant decreases in frequency and dose for both procedural and postprocedural analgesia requirements when using IA lidocaine. Two studies 19,22 However, both studies reported low incidences of grades 2 and 3 RUQP after TACE, and although IA lidocaine was included in the preprocedure medication regimen and may have contributed to RUQP management, these findings must be interpreted with caution as multiple interventions were implemented, and neither study attributes their findings to pre-TACE IA lidocaine alone. It must also be noted that only 3 studies 20Y22 used a visual analog scale as a subjective measurement of pain.…”
Section: Intra-arterial Lidocainementioning
confidence: 96%
“…Selective and superselective injections were performed as necessary and injections were always performed distal to the origin of the gastroduodenal artery. Before chemoembolization, 20 mg lidocaine was administered intra-arterially to reduce pain and discomfort during chemoembolization [9]. Chemoembolization was then performed with a mixture of 20–40 mg doxorubicin (Adriamycin) emulsified with 5 ml of iodized oil (lipiodol) and 1–2 ml of water-soluble iodinated contrast agent (Solutrast).…”
Section: Methodsmentioning
confidence: 99%
“…Intra-arterial injection of lidocaine has been reported to reduce the severity and duration of postembolization pain. 18,19 The usage of corticosteroids to reduce post-embolization pain has been shown to be none beneficial. 19 In our experience, the usage of intravenous analgesics during the procedure and oral analgesics such as Metamizole (Ratiopharm, Ulm, Germany) provide sufficient pain control after chemoembolization.…”
Section: Current Trends In Interventional Treatment Of Colorectal Canmentioning
confidence: 99%
“…The DEBIRI is composed of microspheres that bind irinotecan and release the drug for a period of time after injection at the tumour side. 18 The use of drug-eluting beads results in a lower peak plasma concentration of the chemotherapeutic drugs compared with traditional TACE and longer exposure of the tumour to the therapeutic agents. The lower peak concentration results in lower exposure of healthy liver tissue.…”
Section: Current Trends In Interventional Treatment Of Colorectal Canmentioning
confidence: 99%